EVALUATION OF GREEN OPEN SPACE MANAGEMENT PROGRAM IN GRESIK REGENCY BASED ON CIPP EVALUATION MODEL - Susilo Wati; Andy Fefta Wijaya; Suryadi . (Jurnal Ilmiah Ilmu Administrasi Publik, 2016)
Rapid industrialization gives direct impact on the environmental conditions in Gresik Regency. One attempt to maintain the balance of nature due to the rapid industrialization and rapid urban development is providing enough green open space (GOS) through GOS management program. GOS not only serves to reduce air pollution caused by pollution from existing industry, but also securing the disaster area, oxygen producer, control local climate, water resources and to improve the aesthetics of urban spatial structure. Thus it is important to provide GOS not only for healthy environment but also for sustainable development. By law number 26 of 2007 regarding the Spatial Planning in article 29 states that the proportion of green space in urban areas at least 30 (thirty) percent of the area, where the proportion of public GOS in urban areas at least 20 (twenty) percent of the area, and 10 (ten) percent for private GOS, which it is in line with Gresik local regulation no 10 of 2010 regarding Green Open Space Arrangement. This research used descriptive case study method. The design of this case study is single-case design. The single case study is analogous to a single experiment. This research was conducted in Gresik regency, East Java Province. Gresik regency is known as industrial city in East Java. This condition gives huge impact on environmental degradation especially related to land use.Keywords: Development, Green Open Space, Environment